Life after accusation: Forced internment, human rights violations, and the urgent case for criminalizing witchcraft claims in Ghana - Abubakar Muhammad Jibril; Ramalina Ranaivo Mikea Manitra; Arafat Hossain (Privietlab, 2025)
Accusations of witchcraft in Ghana are still causing forced displacement and severe human rights violations in impoverished, aging women, and other disadvantaged persons. This research is a sociolegal examination of the legal reaction to the protracted crisis in Ghana. Assisted by doctrinal methodology, this article critically examines Ghana's 1992 Constitution, the Criminal Offences Act, 1960 (Act 29), and the Criminal Offences (Amendment) Bill, 2022, against relevant international human rights obligations under the African Charter on Human and Peoples' Rights and the ICCPR. To effectively implement the law, this study employs qualitative data gathered from eight lengthy interviews with survivors, representatives of civil society, religious and traditional leaders, and policymakers. The research indicates that the current criminal law of Ghana offers no clear assurances against unfounded accusations of witchcraft; the bill, nevertheless, makes an effort to close the legislative lacuna by designating malicious accusations as an offence, which is punishable with imprisonment and compulsory compensation. The development has been long due to fostering essential rights relating to security, dignity, and non-discrimination. However, the delay in presidential assent highlights the necessity for continued advocacy. This research demonstrates that the passage of criminalization, alongside systemic reforms, police training, community sensitization programs, and reintegration assistance, is key to bringing forced internment to an end and making Ghana's domestic law consistent with its constitutional obligation and international human rights commitment.